ANALYSIS OF PRE AND POST MERGER FINANCIAL RATIO AT PT INDOSAT OOREDOO HUTCHISON TBK - Windy Atmawardani Rachman (International Journal Management and Economic, 2025)
This study aims to determine the company's financial performance before the merger in 2020-2021 and after the merger in 2022-2023. This study uses quantitative data. The data source used is secondary data. The secondary data used is the Financial Report from the official website of PT Indosat Ooredoo Hutchinson Tbk. The results of the analysis in this study based on the liquidity ratio, Solvability ratio, profitability ratio, and activity ratio are the company's financial performance before and after the merger is in the poor criteria because the average ratio calculation is below the industry standard.